6D.02: GHRELIN RESTORES NITRIC OXIDE AVAILABILITY IN THE FOREARM MICROCIRCULATION OF ESSENTIAL HYPERTENSIVE PATIENTS. (June 2015) - Virdis, A.; Duranti, E.; Lorenzini, G.; Taddei, S.
Abstract : Objective: Essential hypertensive patients (EH) are characterized by endothelial dysfunction caused by a reduced nitric oxide (NO) availability due to reactive oxygen species excess and low-grade inflammatory condition. Ghrelin is a recently identified growth hormone-releasing peptide, with recognized cardiovascular actions. Possible effects on endothelial dysfunction have been never investigated in EH. In this study we evaluated whether exogenous ghrelin can improve endothelial dysfunction in the forearm microcirculation of untreated mild-moderate EH. Design and method: In 9 EH (51.8 ± 8.1 yrs) and 9 normotensive subjects (NS, 50.5 ± 3.5 yrs), we studied the forearm blood flow (FBF, strain-gauge plethysmography) response to intrabrachial acetylcholine (ACh, 0.15–15 mg/100 ml/min) with and without NO synthase blockade by L-NMMA (100 μg/100 ml/min), or the antioxidant vitamin (Vit) C (8 mg/100 ml/min). The protocol was repeated under exogenous ghrelin intra-arterial infusion (200 ng/min, 30' pre-infusion). Results: In NS, the maximal vasodilation (VD) to ACh (480 ± 20%) was inhibited by L-NMMA (292 ± 22, -39 ± 7%; P < 0.001) and unchanged by Vit C (482 ± 34%). Ghrelin failed to modify these vascular responses. In EH, VD to ACh was blunted vs NS (337 ± 45%; P < 0.001) and resistant to L-NMMA (313 ± 32, -7 ± 3%). Vit C increased the response to ACh (509 ± 57%; P < 0.01 vs ACh alone) and restored the inhibiting effect of L-NMMA (332 ± 42, -34 ± 8%; P < 0.001). Ghrelin, while not modifying the basal FBF, it increased (P < 0.001) the VD to ACh (448 ± 55) and restored the inhibitory effect of L-NMMA on ACh (355 ± 43, -20 ± 6%; P < 0.001). Vit C only slightly improved VD to ACh under ghrelin infusion (486 ± 45%). In EH ghrelin significantly (P < 0.05) decreased plasma venous malodialdehyde (from 6.9 ± 1.5 to 5.2 ± 1.0 μmol/L), lipoperoxides (from 9.1 ± 1.9 to 6.6 ± 2.3 μmol/L) and IL-6 (from 11.1 ± 0.6 to 9.3 ± 1.0 pg/mL) and increased plasma antioxidant capacity (from 407 ± 109 to 630 ± 97 mmol/L). Response to sodium nitroprusside was similar between EH and NS and not affected by ghrelin. Conclusions: Exogenous ghrelin is able to increase endothelial dysfunction by restoring NO availability in the forearm microcirculation of EH, an effect probably determined by antioxidant and/or anti-inflammatory activities.